The Creation of a Free Outpatient Surgical Clinic: A Descriptive Report - Natalie Schelbar; Rahel Eshete; Kaya Nies; Robert D Winfield (Journal of Student-Run Clinics, 2024)
Student run free clinics (SRFCs) are continuing to grow in scope and number given the significant benefits to both learners and disadvantaged patients. Despite recent growth, very few provide any form of surgical services. In order to address inequalities in patient access to care and clinical outcomes, it is imperative to include disadvantaged surgical patients, including in the settings of SRFCs. The Kansas City based chapter of Socially Responsible Surgery (SRS) opened a free, volunteer based, student and resident run outpatient surgical clinic. In this article we describe detailed steps to the establishment of the SRS Clinic to lay the framework for other SRFCs or chapters of SRS to continue to grow the number of free clinics able to provide surgical services.